Statistical Long-term Creep Failure Time of Unidirectional CFRP - MIYANO, Yasushi; NAKADA, Masayuki (Materials System, 2017)
A method for statistical prediction of the long-term creep failure time of CFRP using the statistical static strengths of CFRP at various temperatures and the viscoelasticity of matrix resin is proposed based on Christensen's model of viscoelastic crack kinetics. The tensile strength along the longitudinal direction of unidirectional CFRP constitutes important data for the reliable design of CFRP structures. The authors developed a reliable method for testing creep and fatigue strengths as well as static strength at elevated temperatures for resin-impregnated carbon fiber strands (CFRP strands) as unidirectional CFRP. Two kinds of CFRP strands with two types of PAN-based carbon fibers were examined in this study. The statistical static strengths of these CFRP strands and the creep compliances of matrix resins were measured at various temperatures. The tensile creep failure times of these CFRP strands are predicted statistically based on a prediction method using measured data. The predicted creep failure times of these CFRP strands were compared with the creep failure times of these CFRP strands measured experimentally and statistically. Additionally, the statistical temperature-dependent static strengths are also discussed for CFRP strands with pitch-based carbon fibers.